Penggunaan Konjungsi dan Makna Teks Terjemahan Surat Al-Baqarah - Ummul Khair (Indonesian Language Education and Literature, 2018)
The purpose of this study was to 1) describe the type of conjunction in the translation of the sura Al-Baqarah and 2) describe the meaning of the conjunction contained in the surah Al-Baqarah. The method of collecting data uses the read, see, and note method. With basic techniques in the form of determining elements (PUP) techniques, marking reading techniques, and extension techniques. The results of the analysis show: coordinative conjunction dan (78); interfaith conjunction (25); last intra-coordinative sentence conjunction lalu (6); the use of interfaith conjunctions even though padahal (6); coordinative in sentences conjunction tetapi (4); coordinative in sentences conjunction kemudian (4); coordinative in sentences connective bahwa (3); subordinate in sentences conjunction maka (2); subordinate in sentences conjunctions so agar (4); interfaith conjunction selain (2); between interfaith conjunctions lagi (2); subordinate in sentences conjunction ketika (3); subordinate conjunction jika (2); subordinate sub-syntax conjunction jikalau (2); subordinate conjunction sebab (2); subordinate conjunction dengan (2); subordinate conjunction sebagaimana (2). Analysis of the text of the translation of the letter of the Albaqarah juz 1, there are 22 uses of the word conjunction.Tujuan penelitian ini adalah untuk 1) mendeskripsikan jenis konjungsi pada terjemahan surah Al-Baqarah dan 2) memaparkan makna konjungsi yang terkandung dalam surah Al –Baqarah. Metode pengumpulan data menggunakan metode baca, simak, dan catat. Dengan teknik dasar berupa teknik pilah unsur penentu (PUP), teknik baca markah, dan teknik perluas. Hasil analisis menunjukkan: konjungsi koordinatif dan (78); konjungsi antarkalimat (25); konjungsi intra kalimat koordinatif lalu (6); penggunaan konjungsi antarkalimat padahal (6); konjungsi intrakalimat koordinatif tetapi (4); konjungsi intrakalimat koordinatif kemudian (4); kata penghubung intrakalimat koordinatif bahwa (3); konjungsi intrakalimat subordinatif maka (2); konjungsi intrakalimat subordinatif agar (4); konjungsi antarkalimat selain (2); konjungsi antarkalimat lagi (2); konjungsi intrakalimat subordinatif ketika (3); konjungsi subordinatif jika (2); konjungsi intrakalimat subordinatf jikalau (2); konjungsi subordinatif sebab (2); konjungsi subordinatif dengan (2); konjungsi subordinatif sebagaimana (2). Analisis teks terjemahan surat Albaqarah juz 1, terdapat 22 penggunaan kata konjungsi.